CFD Numerical Simulation of Biodiesel Synthesis in a Spinning Disc Reactor - Wen Zhuqing; Petera Jerzy (Chemical and Process Engineering)
In this paper a two-disc spinning disc reactor for intensified biodiesel synthesis is described and numerically simulated. The reactor consists of two flat discs, located coaxially and parallel to each other with a gap of 0.2 mm between the discs. The upper disc is located on a rotating shaft while the lower disc is stationary. The feed liquids, triglycerides (TG) and methanol are introduced coaxially along the centre line of rotating disc and stationary disc. Fluid hydrodynamics in the reactor for synthesis of biodiesel from TG and methanol in the presence of a sodium hydroxide catalyst are simulated, using convection-diffusion-reaction species transport model by the CFD software ANSYS©Fluent v. 13.0. The effect of the upper disc’s spinning speed is evaluated. The results show that the rotational speed increase causes an increase of TG conversion despite the fact that the residence time decreases. Compared to data obtained from adequate experiments, the model shows a satisfactory agreement.